Correction: Machado et al. Cognitive Intervention Strategies Directed to Speech and Language Deficits in Primary Progressive Aphasia: Practice-Based Evidence from 18 Cases. Brain Sci. 2021, 11, 1268 - Thais Helena Machado; Maria Teresa Carthery-Goulart; Aline Carvalho Campanha; Paulo Caramelli (Brain Sciences, 2022)
We would like to have these issues corrected to our recent publication [...]